PENGARUH TARIF, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN TIKET MASKAPAI PENERBANGAN CITILINK - Satrio Pamungkas; Wahyu Hidayat (Universitas Diponegoro, 2017)
Transportation is the most necessary thing in fast-paced era, particularly air transportation. Therefore, the airlines should be able to increase sales in order to survive in this airlines business. PT. Citilink Indonesia District Sales Semarang in selling ticket gain sales increased, but did not achieve sales targets. The purpose of this study is determined the extent of the effect of fare, brand image, and service quality on ticket purchasing decisions Citilink airlines. Type of this research is explanatory research with 100 respondents drawn using purposive sampling technique. The technique of collecting data used questionnaires and interviews. The analytical method in this research used regression analysis with SPSS version 20.0. The results showed that the rate has an effect on purchasing decisions with a correlation coefficient of determination coefficient of 0.667 and 19.6%, brand image has an effect on purchasing decisions with a correlation coefficient of 0.493 and a coefficient of determination of 24.3%, service quality has an effect on purchasing decisions with coefficients 0.609 correlation coefficient of determination and 37.1%. Fare, brand image, and service quality together have an effect on purchasing decisions by the equation Y = 0,464 + 0,275 X1 + 0,054 X2 + 0,144 X3. This means that the effect of fare, brand image, and service quality will improve purchasing decisions. Advices for the company based on this research are needed to provide clearer information about discounting, providing promotional rates in order to attract customers, can display the image distinct and different from the others, so it will further strengthen its brand image, and service on time performance (OTP) must be addressed and corrected, so there’s not delay on the flight schedule.